Lives in the Asylum Record, 1864 to 1910: Utilising Large Data Collection for Histories of Psychiatry and Mental Health. Issue 3 (12th June 2017) - McCarthy, Angela; Coleborne, Catharine; O'Connor, Maree; Knewstubb, Elspeth
Abstract : This article examines the research implications and uses of data for a large project investigating institutional confinement in Australia and New Zealand. The cases of patients admitted between 1864 and 1910 at four separate institutions, three public and one private, provided more than 4000 patient records to a collaborative team of researchers. The utility and longevity of this data and the ways to continue to understand its significance and contents form the basis of this article's interrogation of data collection and methodological issues surrounding the history of psychiatry and mental health. It examines the themes of ethics and access, record linkage, categories of data analysis, comparison and record keeping across colonial and imperial institutions, and constraints and opportunities in the data itself. The aim of this article is to continue an ongoing conversation among historians of mental health about the role and value of data collection for mental health and to signal the relevance of international multi-sited collaborative research in this field.